2021
DOI: 10.2196/23863
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Limitation of Machine Learning Algorithms for Diabetic Retinopathy Screening: Meta-analysis

Abstract: Background Diabetic retinopathy (DR), whose standard diagnosis is performed by human experts, has high prevalence and requires a more efficient screening method. Although machine learning (ML)–based automated DR diagnosis has gained attention due to recent approval of IDx-DR, performance of this tool has not been examined systematically, and the best ML technique for use in a real-world setting has not been discussed. Objective The aim of this study was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 78 publications
0
33
0
2
Order By: Relevance
“…Talkwalker cannot carry out such an interpretation, which aligns with a number of studies that have pointed out the limitations of machines. Although machine learning methods have been developed to solve real-world problems, they are not sufficient by themselves in critical decision-making approaches [ 38 , 39 ]. Digital platforms still have limitations to interpret and contextualize data [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Talkwalker cannot carry out such an interpretation, which aligns with a number of studies that have pointed out the limitations of machines. Although machine learning methods have been developed to solve real-world problems, they are not sufficient by themselves in critical decision-making approaches [ 38 , 39 ]. Digital platforms still have limitations to interpret and contextualize data [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…From a medical perspective, the availability of structured data builds the base for additional tools, such as machine learning algorithms (e.g., [ 23 ]) and decision support systems (e.g., [ 24 , 25 ]), which result in suggestions for diagnostic and therapy options, especially, but not limited to, diabetes-related eye-diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the mechanisms underlying decision-making are different in algorithms and clinicians. The grading criteria of the automatic systems may have been more demanding than those of the humans, but what is evident is that their implementation is invariable and not affected by the inherent inconsistency of human subjectivity [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…IDx-DR v2 achieved 100% sensitivity and 81.82% specificity for derivable DR and 100% sensitivity and 94.64% specificity for STDR in the sample examined [ 38 ]. A meta-analysis demonstrated that ML algorithms have a high diagnostic accuracy for the diagnosis of DR on color fundus photographs suggesting that they may also be ready for clinical application in screening programs [ 29 ]. However, early results published in relation to this ML had methodological inconsistencies, such as lack of external validation and the presence of biases.…”
Section: Discussionmentioning
confidence: 99%